The Effectiveness of Teacher Professional Education Program in English Teaching - Novi Berliana Sukoco; Dila Charisma; Eline Rozaliya Winarto (UM Purwokerto Press, 2024)
This study aimed to document the alumni of the Teacher Certification Program at the two of Universities in Cirebon regarding the effectiveness of the PPG program in preparing professional English teachers. The design was a survey under the quantitative approach. The program's effectiveness was assessed based on four main aspects: Learning Materials, Learning Evaluation, Lesson Planning, and Learning Media. This study involved all PPG alumni in the academic year 2023, with a total of 50 respondents. Data were collected through a Google Form-based survey that adopted the PPG program evaluation questionnaire. In terms of learning materials, 71% of alumni stated that the PPG helped them improve their mastery of the material and teaching quality, as well as making them feel more prepared to teach effectively. Conversely, only 29% agreed. Regarding learning evaluation, 59% of alumni strongly agreed that the PPG enhanced their ability to evaluate student learning, understand various evaluation methods, and boost their confidence in conducting evaluations, while the rest agreed. In the aspect of lesson planning, 63% of alumni strongly agreed that the PPG enhanced and developed their ability to design engaging and varied lessons. Concerning learning media, 63% of alumni also strongly agreed that the PPG helped them improve the use of learning media, student engagement, and understanding of effective ways to use learning media to support the student learning process. This research showed that 72% of alumni believed that the PPG program had a significant impact on enhancing teacher professionalism, with the greatest impact seen in the aspects of professional and pedagogical competence. This study also indicated that there are several aspects that need to be considered by PPG organizers for future program improvements.